Respon Tanaman Jagung (Zea mays) pada Beberapa Jarak Tanam dan Komposisi Pemupukan - Muhsanati, Muhsanati; Dwipa, Indra; Hasibuan, Muhammad Revan (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2022)
The study about response of maize (Zea mays) to various plant spacing and fertilizers composition. This research aims to determine the interaction between spacing and composition of chicken manure with NPK fertilizer. In addition, determining the spacing and composition of chicken manure with the best NPK fertilizer on the growth and yield of maize. This research was conducted from February to June 2020 in Limau Manis, Padang City. The design used was a factorial design arranged in a Randomized Block Design (RBD) with 2 factors. The first factor is the spacing which consists of 3 levels of treatment (70 cm x 20 cm; 70 cm x 30 cm; and 70 cm x 40 cm). The second factor is the composition of chicken manure with NPK fertilizer which consists of 4 treatment levels (5 + 50; 10 + 100; 15 + 150; and 20 tons ha-1 + 200 kg ha-1). The research data were analyzed statistically with the F test at the 5% level. The results showed that there was no interaction between spacing and composition of chicken manure with NPK fertilizer. Spacing 70 cm x 20 cm is the spacing that has the best growth and yield, while the composition of chicken manure 20 tons ha-1 with NPK 200 kg ha-1 is the composition of the fertilizer that has the best growth and yield.